Information Source Quality in Intelligent Transport Systems - Jelušić, Niko; Anžek, Mario; Ivanković, Božidar (Promet - Traffic&Transportation, 2012)
Advanced automatic traffic control systems and various other ITS (Intelligent Transport Systems) applications and services rely on real-time information from the traffic system. This paper presents the overview and general functions of different information sources which provide real-time information that are used or could be used in ITS. The objective is to formally define the quality of information sources suitable for ITS based on formal models of the traffic system and information sources. The definition of quality encompasses these essential factors: traffic system information that exists or may be requested, user requirements and attributes that describe the information sources. This provides the framework and guidelines for the evaluation of information sources that accounts for relevant factors that influence their selection for specific ITS applications.KEY WORDS: information source, information source quality, Intelligent Transport Systems (ITS), automatic traffic control